Sex, desire and masturbation : An interpretative phenomenological analysis of sexual health education for young women - Hanson, Jodie (Manchester Metropolitan University, 2014)
British, Sex and Relationship Education has been condemned by Ofsted as ‘not yet good enough’ (2013:6). Previous literature would suggest this is through the absence of desire based knowledge. Other research would highlight the issue of masturbation as a construct to the improvement of the sexual health. However, as genital masturbation is often a taboo within feminine culture the current study used Interpretative Phenomenological Analysis (Smith, 1996, 1999) to assess the intrinsic values of six young women regarding their sexual health and desires. Participants ranged in sexual knowledge from undergone several years of sexual health education to limited sexual health education; forming the basis for the current national education system. Analysis of the data revealed three master themes: pleasure conflict, ‘That Girl’ complex and sexual discourse. A working model of sexual health needs was then proposed in order to address the hierarchy of erotic plasticity the participants showed. Ramifications of socio-political implications towards feminine desire and masturbation are detrimental to sexual health improvement.
Keywords: 2000 à aujourd'hui; 2010-2019; angleterre; discipline; europe; jeunes femmes*; masturbation féminine; mémoires/thèses; périodes historiques; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; sexualité des femmes*; thématiques; éducation sexuelle; études qualitatives